Cardiovascular disease risks in younger versus older adult B‐cell non‐Hodgkin's lymphoma survivors. (12th May 2021) - Ocier, Krista; Abdelaziz, Sarah; Kim, Seungmin; Rowe, Kerry; Snyder, John; Deshmukh, Vikrant; Newman, Michael; Fraser, Alison; Smith, Ken; Porucznik, Christina A.; Shoaf, Kimberley; Stanford, Joseph B.; et al.
Abstract: Introduction: Young cancer survivors may be at increased risk of early‐onset chronic health conditions. The aim of this population‐based study is to estimate cardiovascular disease (CVD) risk among younger versus older B‐cell non‐Hodgkin's lymphoma (B‐NHL) survivors compared with their respective general population cohorts. Methods: B‐NHL survivors diagnosed from 1997 to 2015 in the Utah Cancer Registry were matched with up to five cancer‐free individuals on birth year, sex, and birth state, using the statewide Utah Population Database. Electronic medical records and statewide health care facility data were used to identify disease outcomes ≥5 years after cancer diagnosis. Cox Proportional Hazards models were used to estimate hazard ratios for B‐NHL survivors diagnosed at <65 years and ≥65 years old. Results: Younger B‐NHL survivors had higher relative risks than older cancer survivors of chronic rheumatic disease of the heart valves (HR = 4.14, 99% CI = 2.17–7.89; P valueheterogeneity = 0.004); peri‐, endo‐, and myocarditis (HR = 2.43, 99% CI = 1.38–4.28; P valueheterogeneity = 0.016); diseases of the arteries (HR = 1.63, 99% CI = 1.21–2.21; P valueheterogeneity = 0.044); and hypotension (HR = 2.44, 99% CI = 1.58–3.75; P valueheterogeneity = 0.048). B‐NHL survivors of both age groups had elevated relative risks of heart disease overall and congestive heart failure. Conclusion: Younger B‐NHL survivors had higher risks than older B‐NHL survivors of specific cardiovascular diseases compared to their respective general population cohorts. Abstract : This population‐based study demonstrates elevated cardiovascular disease risks in B‐NHL survivors (<65 vs. ≥65 years old) relative to their general population cohorts, suggesting that early aging among younger B‐NHL survivors may warrant an assessment of long‐term health effects as part of cancer survivorship care. ​